The role of color in recognizing material changes - Yoonessi, Ali (2010)
The chemical and physical properties of objects provide them with specific surface patterns of color and texture. Endogenous and exogenous forces alter these colors and patterns over time. The ability to identify these changes can have great utility in judging the state and history of objects. To evaluate the role of color cues in this process, we used images of 26 materials undergoing real changes. Observers were asked to identify materials and types of changes for color and gray-scale images. The images were shown in three sets; one image of the surface, two images of the same surface before and after a natural change, and image sequences of the time-varying appearance. The presence of color cues improved performance in all conditions. Identification of materials improved if observers saw two states of the material, but the complete image sequence did not improve performance.